Functional Calculation of a Driving Mechanism of a Handling Machine for Disabled Persons - Kurcik, Pavol; Blatnicky, Miroslav; Dizo, Jan (Manufacturing Technology Journal, 2019)
This article deals with state-of-art in the field of handling machines intended for disabled people, which serve for disabled entry of such people and for people with delimited locomotion. It contains calculation of forces, which act in the mechanical system of an electric device during its operation in real conditions, changes of reactions depending on the load and the climbing angle as this solved handling machine will designed for negotiation of staircases. The objective is the functional calculation of a driving mechanism of a stair chair marked SA Alfa, i. e. the calculation of loading forces and their action on the driving mechanism. It will serve in the next step as an input for the calculation of a required power under conditions of occurance of maximal resistance forces, which will be determining factor for dimensioning of driving components of this device.
Keywords: Handling machine; Disabled persons; Functional calculation; Driving mechanism